Exploration of treatment strategies for normal cytology smears with reactive cellular changes. (November 2015) - Yang, Jin; Wu, Dan; Li, Zhunan; Wu, Jiahao; Ding, Li; Xu, Ying
Abstract: Objective: To evaluate the use of high-risk humanpapillomavirus (HR-HPV) DNA testing in women who have normal cytology result with reactive cellular changes to identify high risk patients of developing precancerous cervical lesions and cervical cancer. Study design: Outpatient patients with normal liquid-based cytology (LCT) results showing reactive cellular changes (case group, n = 1085) and normal LCT without reactive cellular changes (control group, n = 1085) were recruited from cervical clinics at the International Peace Maternity & Child Health Hospital from January 2012 to December 2013. The HPV status and cervical biopsy pathology results were analyzed. Results: The HR-HPV positive rate of the case group (598/1085) was higher than that of the control group (163/1085) ( P < 0.001). HR-HPV prevalence among CIN1, CIN2, CIN3 and cervical cancer was 73%, 87%, 100%, and 100% respectively ( P < 0.05). In patients with positive HR-HPV results, more CIN2+ were found significantly in case group (37/598) than those in control group (3/163), P = 0.027. The sensitivity of diagnosis of CIN2+ lesions by HR-HPV testing was 92.5%, the specificity was 36%, the positive predicted value was 8.6%, and the negative predictive value was 98.6%. The incidence of CIN2+ lesions was not different among different age groups ( P > 0.05). Conclusion: Reactive cellular changes in normal cervical smears should be further investigated. HR-HPV testing could be used as an effective triage in cases of reactive cellular changes. Colposcopy is recommended for those cases showing reactive cellular changes combined with HR-HPV positivity to reduce the risk of failure to diagnose cervical cancer and precancerous lesions.